The effect of urinary incontinence and sexual dysfunction on the quality of life among people with multiple sclerosis - Loureiro, A. P. (2017)
Introduction/Background - Urinary incontinence and sexual dysfunction are frequent clinical manifestations in Multiple Sclerosis (MS) sufferers, of great social impact, but their impacts on the quality of life of these people are not always recognized and evaluated. This study aims to investigate if there are any differences between Brazilian and Portuguese MS populations for the scores obtained in the Multiple Sclerosis Quality of Life – MSQOL-54 questionnaire for the sexual function and social function questions. Material and Methods - 58 individuals with MS (average age of 38.57±12.02; average diagnosis time of 6.28 years) living in Curitiba, Brazil; and 280 individuals with MS (average age of 39.23±(11.21; average diagnosis time of 7.21 years) living in Lisbon, Portugal, took part in this study. Women predominated in both the groups living in Curitiba (72.4%) and in Lisbon (71.4%). Results - The values obtained for sphincter incontinence X social function, described by their medians (1Q-3Q) were 100.0 (75.0 – 100.0) for the Brazilian population and 75.0 (50.0 – 100.0) for the Portuguese population; showing a 25% higher score amongst the Brazilians (p = 0.046 – Mann Whitney). There was no difference for the sexual function score (p = 0.156 – Mann Whitney) with values of 66.7 (45.0 – 80.0) for the Brazilians and 66.7 (33.3 – 80.0) for the Portuguese. Conclusion - It was observed that sexual function interfered with the quality of life of the two populations studied in a similar way, and that the influence of problems caused by sphincter disorders on social life were of a lower level for the participants from Lisbon. Thus it is suggested that intervention programs focused on sexual and sphincter adjustments are necessary for both populations.